Cost and Time Reduction of Industrial Mold Design and Manufacturing by Implementing Additive Manufacturing for Premature Neonatal Prong - Mirnia, Kayvan; Kialashaki, Atousa; Heidarzadeh, Mohammad; Maghsoudi, Amid; Pourashouri, Zahra; Abaei Kashan, Abbas (Current Pediatric Reviews, 2024)
Introduction: For a long time, molding was one of the most important methods of producing metal, ceramic, and polymer materials. The two essential factors in this method were always cost and time. Technology advancements have made it possible to design in 3D using a computer and additive manufacturing. This article covers methods for using 3D printers to save time and money in the process of creating the final product. The “Prong” molds for premature neonatal respiratory aid were designed and produced based on neonatologists' considerations. Methods: The study was conducted on fifteen very low birth neonates at Alzahra Hospital in Tabriz University from September 2017 to September 2019. In the first section, we described dental plaster material for molding. When using this material, the printing material must be selected and the parameters, like melting temperature and printer speed, must be controlled to achieve acceptable quality for the final sample. CAD software can be used to print various objects if the final 3D design is appropriate. Results: We used additive manufacturing technology to create a new design and successfully resolved bubble issues at a low cost through a combination of creativity and experimentation. The new mold has cavities that allow the silicon to occupy the entire space and escape any bubbles. Conclusion: The use of 3D printers allows us to achieve the best design for the prong mold while reducing both production costs and time. The ultimate mold made of aluminum was finally produced by the CNC machine. The final product was tested at Al-Zahra Hospital in Tabriz, Iran, and the results were satisfactory, with no reports of necrosis on the babies' noses.
Keywords: necrosis